KONTRADIKTIF HADIS HUKUM ZIARAH KUBUR PERSPEKTIF FILSAFAT HUKUM ISLAM - Nurhadi Nurhadi (Institut Agama Islam Negeri (IAIN) Kendari, 2019)
The tomb pilgrimage is to visit someone's grave with the intention of praying for him and take the lesson someday. Including sunnah pilgrimage to the tomb of the Prophet and will get intercession from him. In the beginning of Islam, the pilgrimage of the grave was forbidden by the Shari'ah. The wisdom of the prohibition of the grave pilgrimage before its disyari'at, namely because the companions of that period were still close to the time of ignorance. The purpose of the grave pilgrimage is to provide benefits to the grave pilgrims, namely to take ibrah, soften the heart, remind death and remind of the existence of the hereafter. Besides that it also benefits the inhabitants of the tomb, namely greetings (do'a) from the pilgrims. The law of pilgrimage is the sunnah. When the grave pilgrimage (do'a) salam to the grave expert, do not sit on the grave and step on it, do not slaughter animals in the grave, may not bernadzar to people who have died in the cemetery and so forth. The pilgrimage of the grave is not bid'ah because the Messenger of Allah made a pilgrimage to the grave of his mother.